2003
DOI: 10.1046/j.1432-1033.2003.03408.x
|View full text |Cite
|
Sign up to set email alerts
|

The transthyretin‐related protein family

Abstract: A number of proteins related to the homotetrameric transport protein transthyretin (TTR) forms a highly conserved protein family, which we present in an integrated analysis of data from different sources combined with an initial biochemical characterization. Homologues of the transthyretinrelated protein (TRP) can be found in a wide range of species including bacteria, plants and animals, whereas transthyretins have so far only been identified in vertebrates. A multiple sequence alignment of 49 TRP sequences f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
93
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 59 publications
7
93
1
Order By: Relevance
“…In lamprey, one TTR was recently cloned from two species, P. marinus and L. appendix (Manzon et al, 2007), and expression correlated with metamorphosis. This suggests a deeper ancestry for TTR than previously thought (Eneqvist et al, 2003). In amphioxus and in Ciona, virtually nothing is known about TH transport.…”
Section: Th and Th Derivative Transport In Chordatesmentioning
confidence: 80%
“…In lamprey, one TTR was recently cloned from two species, P. marinus and L. appendix (Manzon et al, 2007), and expression correlated with metamorphosis. This suggests a deeper ancestry for TTR than previously thought (Eneqvist et al, 2003). In amphioxus and in Ciona, virtually nothing is known about TH transport.…”
Section: Th and Th Derivative Transport In Chordatesmentioning
confidence: 80%
“…Overall, PucM and TTR share many structural features, but their different chemical identities and the size of the active site resulting from the sequence differences sharply distinguish the functions of these two structural homologs. Previous phylogenetic analysis has suggested that TRPs and TTRs belong to separate branches, and that TRP, an ancestor of TTR, has been conserved whereas TTR has evolved independently in vertebrates (12).…”
Section: Discussionmentioning
confidence: 99%
“…PucM from B. subtilis consists of 121 aa and shows 55% sequence similarity with a functionally unrelated protein, transthyretin (TTR), a thyroid hormone-binding protein in vertebrates (12,13). Because of these sequence similarities, PucM has been classified as a member of the TTR-related protein (TRP) family.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HIU hydrolase is a member of the transthyretin-related protein (TRP) family, which displays high sequence conservation throughout evolution (9). Current evidence suggests that TRP family members act as HIU hydrolases in bacteria and that the product of the Urah gene performs this biochemical function in mice (1,10,11), catalyzing the second of three steps in the conversion of uric acid to allantoin (Fig.…”
Section: Platelet 2 An Enu-induced Mutation Causing Thrombocytosis Andmentioning
confidence: 99%